Detailed characterization of the mRNA mapping in the HindIII fragment K region of the herpes simplex virus type 1 genome. - Anderson, K P (1981)
We have isolated as recombinant DNA clones, in the plasmid pBR322, regions of the herpesvirus type 1 genome spanning the region between 0.53 and 0.6 on the prototypical arrangement. This 11,000-base-pair region corresponds to 10% of the large unique region and encodes five major and several minor mRNA species abundant at different times after infection, which range in length from 7 to 1 kilobase. In this report, we have used RNA transfer blots and S1 nuclease digestion of hybrids between viral DNA and polyribosomal RNA to precisely localize (+/- 0.1 kilobase) these mRNA's. Comparison of neutral and alkaline gels of S1 nuclease-digested hybrids indicates no internal introns in the coding sequences of these mRNA's, although noncontiguous leader sequences near (ca. 0.1 kilobase) the 5' ends of any or all mRNA's could not be excluded. The 5' ends of several late mRNA's that are encoded opposite DNA strands map very close to one another, and the 3' ends of a major late and a major early mRNA, which are partially colinear, terminate in the same region. In vitro translation of the viral mRNA's isolated by hybridization with DNA bound to cellulose and fractionation of mRNA species on denaturing agarose gels allowed us to assign specific polypeptide products to each of the mRNA's characterized. Among other results, it was demonstrated unequivocally that two major late mRNA's, which partially overlap, encode the same polypeptide.